Feasibility Study of the Remote Operation Centre (ROC) for Autonomous Power Plants - Ibraheem, Diana (My University, 2025)
Autonomous operation of distributed power assets requires a remote operation center (ROC) that integrates sensing, control and assurance with auditable execution. This thesis defines and implements a ROC reference architecture for autonomous power plants, emphasizing deterministic supervision, explainable autonomy and operator-in-the-loop authority. The design draws on established standards and technologies: measurement and calibration workflows, time synchronisation (PTP/NTP), interoperable interfaces, and the data plane that supports multi-rate fusion, digital-twin synchronisation and embedded-grade cybersecurity. The control stack combines model-predictive control and reinforcement learning, bounded by safety envelopes, action-admissibility checks and traceable logging to preserve transparency and rollback capability. The architecture is evaluated in the EPS/VEBIC laboratory against timing and data-integrity constraints, demonstrating end-to-end timing fidelity, fault-tolerant acquisition and the feasibility of deterministic supervisory control as a base for higher autonomy. The main contribution is an implementable ROC blueprint that links measurement integrity, secure communications and hierarchical control to an auditable route from remote supervision to safe autonomy. The work is limited to architectural design and laboratory-based validation; a formal safety case and comprehensive verification and validation of AI components remain future work, alongside scaling to multi-asset supervision.
Keywords: power plants; autonomous systems; artificial intelligence; control systems; reinforcement learning; control rooms; synchronising; cyber security; Sustainable and Autonomous Systems; Master's Programme in Sustainable and Autonomus Systems (SAS)